Empathy, remorse, and restoration of dignity contributing to reduced recidivism: assessing the role of restorative justice in promoting offender rehabilitation and reintegration in Durban - Zandile Faith Mpofu; Sazelo Michael Mkhize; James Udoh Akpan (Cogent Social Sciences, 2024)
This study aims to determine whether restorative justice (RJ) programmes can help reduce recidivism and facilitate the effective reintegration of offenders into society by encouraging empathy, regret, and the restoration of their dignity. The research investigates the lived experiences of key informants and community members in Cato Manor, South Africa, using a qualitative methodology approach. The significance of restorative justice (RJ) programmes in fostering possibilities for regret among offenders and a feeling of community connection was demonstrated using thematic analysis. These results support the Social Bond Theory (SBT) and Reintegrative Shaming Theory (RST), indicating that restorative justice (RJ) can promote accountability and lower recidivism rates. Families must take an active role in helping offenders get back on track and reintegrate into society through therapy and support services. To guarantee the efficacy of RJ programmes and to ensure that they address the unique requirements of the community, the study highlights that there is a necessity of involving community members in their design and evaluation. RJ programmes can provide a route to a more efficient and compassionate judicial system by emphasising communication, healing, and reintegration; this will ultimately lead to safer and more equitable societies. The study’s conclusions advocate for a comprehensive strategy to lower recidivism, one that includes active community involvement in RJ efforts, family assistance, focused interventions, and career counselling for ex-offenders.